2023
DOI: 10.1101/2023.02.01.23285183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between increased anterior cingulate glutamate and psychotic-like symptoms, but not autistic traits

Abstract: BackgroundDespite many differences, autism spectrum disorder and schizophrenia spectrum disorder share environmental risk factors, genetic predispositions as well as neuronal abnormalities, and show similar cognitive deficits in working memory, perspective taking, or response inhibition. These alterations are already present in subclinical traits of these disorders. The literature proposes that alterations in the inhibitory GABAergic and excitatory glutamatergic system could explain underlying neuronal commona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 94 publications
1
1
0
Order By: Relevance
“…One study reported higher levels (28), whereas others found reductions (2931) or no significant differences (32,33) in first-episode psychosis or schizophrenic patients in the ACC. The same irregularity can be found for subjects at risk for psychosis, in the ACC higher (4,11,3436) and lower (10) glutamate levels, or even no significant results (3739) have been described. Besides the differences between patient groups, even of the same disease stage (e.g., due to medication status), exact voxel placement, and acquisition with different scanner hardware; one problem, adding heterogeneity to the results, could be the choice of the components of a basis set.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…One study reported higher levels (28), whereas others found reductions (2931) or no significant differences (32,33) in first-episode psychosis or schizophrenic patients in the ACC. The same irregularity can be found for subjects at risk for psychosis, in the ACC higher (4,11,3436) and lower (10) glutamate levels, or even no significant results (3739) have been described. Besides the differences between patient groups, even of the same disease stage (e.g., due to medication status), exact voxel placement, and acquisition with different scanner hardware; one problem, adding heterogeneity to the results, could be the choice of the components of a basis set.…”
Section: Introductionsupporting
confidence: 54%
“…Due to the varying TE in our 1 H-MRS data between and within the individual voxels, we utilized MARSS in INSPECTOR version 11-2021 (40) to generate six distinct PRESS basis sets for each TE (36, 37, 38, 39, 40, 41), employing a bandwidth of 2000Hz and 1024pts in each simulation. Based on the literature, we selected five different exemplar basis set compositions for illustration.…”
Section: Methodsmentioning
confidence: 99%